2016
DOI: 10.1016/j.biopsych.2015.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking GPR88 Show Motor Deficit, Improved Spatial Learning, and Low Anxiety Reversed by Delta Opioid Antagonist

Abstract: Background GPR88 is an orphan G protein coupled receptor (GPCR) highly enriched in the striatum, and previous studies have focused on GPR88 function in striatal physiology. The receptor is also expressed in other brain areas and here we examined whether GPR88 function extends beyond striatal-mediated responses. Methods We created Gpr88 knockout mice and examined both striatal and extra-striatal regions at molecular and cellular levels. We also tested striatum, hippocampus- and amygdala-dependent behaviors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
194
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(213 citation statements)
references
References 70 publications
19
194
0
Order By: Relevance
“…In a different study, GPR88-deficient mice exhibited increased locomotion, poor motor coordination and impaired cue-based learning, which could be normalized by targeted viral expression of the receptor in striatal MSNs [8]. A recent study also linked GPR88 to anxiety disorders, as the GPR88-knockout mice exhibited low anxiety compared to wild-type animals [13]. …”
Section: Introductionmentioning
confidence: 99%
“…In a different study, GPR88-deficient mice exhibited increased locomotion, poor motor coordination and impaired cue-based learning, which could be normalized by targeted viral expression of the receptor in striatal MSNs [8]. A recent study also linked GPR88 to anxiety disorders, as the GPR88-knockout mice exhibited low anxiety compared to wild-type animals [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study showed that the GPR88-deficient mice performed better in spatial tasks and reduced levels of anxiety, indicating GPR88 may also play a role in cognitive and anxiety disorders. 11 …”
mentioning
confidence: 99%
“…14 Given its favorable calculated physiochemical properties (clogP = 4.53, TPSA = 64.35, logBB = −0.12) 1517 and GPR88-specific activity in the striatum, 11 2-AMPP is a promising lead for further optimization to probe GPR88 in vivo functions. In order to gain the SAR information of 2-AMPP for high potency, we have synthesized a series of analogues with structural modifications at sites A and B (Figure 1) and evaluated their agonist activity at GPR88.…”
Section: Resultsmentioning
confidence: 99%
“…48 Genetically-modified mice that lack GPR88 expression exhibit enhanced response to dopaminergic agonists and altered performance in models relevant to schizophrenia and anxiety, indicating that GPR88 may have a potential therapeutic role in treating these CNS disorders. 911 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation